2021
DOI: 10.7759/cureus.18364
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Adverse Outcome Factors of Severe Acute Malnutrition in Children: A Hospital-Based Study in Odisha

Abstract: BackgroundMalnutrition is prevalent in 41% of children less than five years old in developing countries. ObjectiveTo determine the clinical spectrum, identify the risk factors, and find out the factors responsible for the adverse outcomes of severe acute malnutrition (SAM) in children. MethodsIn this prospective cohort, children aged one month to five years with SAM from October 2016 to September 2018 were enrolled. Clinical profile, contributing factors, treatment, and outcome of cases (n=198) were noted. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…Consequently, relying solely on breast milk may not suffice to provide the necessary nutrients for optimal growth. These findings are consistent with those of Das et al 20 where inappropriate introduction of complementary feeding was similarly found to be significantly associated with SAM. Notably, our study revealed that only 50% of participants introduced complementary feeding in a timely manner, a rate lower than the regional average of 66.7% 7 .…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, relying solely on breast milk may not suffice to provide the necessary nutrients for optimal growth. These findings are consistent with those of Das et al 20 where inappropriate introduction of complementary feeding was similarly found to be significantly associated with SAM. Notably, our study revealed that only 50% of participants introduced complementary feeding in a timely manner, a rate lower than the regional average of 66.7% 7 .…”
Section: Discussionsupporting
confidence: 93%
“…The recovery rate of the current study is lower than the Sphere Standard acceptable ranges (mortality < 3%, default < 15%, and recovered > 75%), 37 and to what is reported by several studies of the same nature. 38–42 However, it is comparable to other studies reporting recovery rates from SAM. 43–47 The conflicts of the recovery rates are attributed to the difference in settings where the OTP program was offered which is not the same in various healthcare settings.…”
Section: Discussionsupporting
confidence: 85%
“…In a study conducted by Jena et al SAM was more common in children aged 6 months to 1 year. 22 Prevalence of SAM was found to be equal amongst male and female patients in our study. Similarly in a study conducted by Das et al by there was no variation in sex.…”
Section: Discussionsupporting
confidence: 49%